Natural Terrestrial Environment from Selected Field Data Measurements: Results and Applications for Launch Vehicle Development - Johnson,Dale L. (2017)
ABSTRACT: This paper is mainly a review presenting 3 unique NASA natural environment field projects. Included are some important natural environment technical results and applications that are applicable in the design, development and operations of launch vehicles as well as in advancing the atmospheric state-of-the-art. For the design, development, testing, launch and flight of various launch vehicles all natural terrestrial environments are considered, with normally wind being the main contributor or driver to the design of a launch vehicle.